2019
DOI: 10.1111/jvh.13238
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of hepatitis C virus infection in a country with universal access to direct‐acting antiviral agents: Data for designing a cost‐effective elimination policy in Spain

Abstract: Accurate HCV prevalence estimates are necessary for guiding elimination policies. Our aim was to determine the HCV prevalence and assess the cost‐effectiveness of a screen‐and‐treat strategy in the Spanish population. A population‐based, cross‐sectional study (PREVHEP‐ETHON Cohort, Epidemiological sTudy of Hepatic infectiONs; NCT02749864) was performed from July 2015‐April 2017. Participants from three Spanish regions were selected using two‐stage conglomerate sampling, and stratified by age, with randomized s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 29 publications
(67 reference statements)
1
25
0
4
Order By: Relevance
“…This study has several limitations that could affect the robustness sectional study in Spain found that a stepwise screening strategy, similar to the graduated screening 1 scenario described here, was cost saving, 28 supporting that this type of strategy may be feasible.…”
Section: Limitationssupporting
confidence: 50%
“…This study has several limitations that could affect the robustness sectional study in Spain found that a stepwise screening strategy, similar to the graduated screening 1 scenario described here, was cost saving, 28 supporting that this type of strategy may be feasible.…”
Section: Limitationssupporting
confidence: 50%
“…Considering the high prevalence of these infections, such infection-related increase of risk of PD may affect a quite large population. For example, HCV was reported to affect 0.3% of population in Spain (Crespo et al, 2019), HP colonizes the gastric mucosa of more than half of the global human population (Suwarnalata et al, 2016), Malassezia was identified on more than 80% lesional skin (Arsic Arsenijevic et al, 2014), HBV affects 2 billion people worldwide and over 360 million chronic carriers (Yankam, Anye, Nkfusai, Shirinde, & Cumber, 2019). Therefore, clarification of the effect of such infection on risk of PD may assist the prevention and prediction of PD and bring benefits to a large population.…”
Section: Introductionmentioning
confidence: 99%
“…The study has some limitations that could involve selection and participation bias that have been previously discussed 6 . We cannot rule out some misclassification in the stage of infection due to the study design.…”
Section: Discussionmentioning
confidence: 95%
“…We cannot rule out some misclassification in the stage of infection due to the study design. The sample size calculation was based on estimated slightly higher values of the prevalence figures for each age stratum 6 ; therefore, a larger number of subjects were studied, which helps provide a more accurate estimation of the parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation